TEXT-BASED APPROACH TO EFL TEACHING AND LEARNING ACTIVITY - Putri, Lestari Tri; Apriansi, Mardia (Corolla International Conference, 2022)
Text-based approach to learning English as a foreign language using text as a basis for developing learning programs. This approach has been used in Indonesia since the application of the Competency Based Curriculum. This approach was developed from Waliday Functional Linguistics and refers to the provision of information about the development of effective texts for specific purposes in the context of real language usage. In this text-based approach, learning is carried out in two cycles namely the oral and writing cycle. Each cycle consists of four stages, namely building context, modeling, constructing guided texts, and constructing independent texts. This framework can accommodate new thoughts and innovations in learning English as a foreignlanguage in Indonesia. Thus it is very suitable to be applied by teachers who are creative and innovative for improvement and improvement of learning English as a foreign language in Indonesia.